Estimation of stoichiometric and kinetic coefficients of ASm3 under aerobic and anoxic conditions via respirometry - Avcioğlu, E.; Karahan-Gül, O.; Orhon, D. (IWA Publishing, 2003)
Activated Sludge Model No.1 (ASM1) has been used extensively for the design and simulation of biological treatment systems. Batch respirometric experiments have been described in the model for the determination of model coefficients and respirometric studies have been proved to be useful in kinetic parameter estimation and wastewater characterisation for ASM1. Activated Sludge Model No. 3 (ASm3) has also introduced a number of kinetic and stoichiometric coefficients with the new processes defined in the model, also suggesting some default values. Recent studies on the application of ASm3 are limited to special cases in terms of parameter determination. Proper calibration of ASm3 parameters can be a difficult task without involving respirometric procedures as experimental tools. Respirometric batch tests were conveniently used in this study in order to estimate ASm3 parameters and the main kinetic and stoichiometric model coefficients were successfully and uniquely determined for aerobic and anoxic conditions for acetate.
Keywords: Sewage; Reproducibility of Results; Models, Theoretical; Waste Disposal, Fluid; Oxygen; Kinetics; Bioreactors; Calibration